Electronic cigarette use and chest pain in US adults: Evidence from the PATH study - Leili Behrooz; Wubin Xie; Aboli Goghari; Rosemarie Robertson; Aruni Bhatnagar; Andrew Stokes; Naomi M. Hamburg (Tobacco Induced Diseases)
Introduction Electronic cigarettes (e-cigarette) were introduced for smoking cessation/reduction but have also become popular among the youth. Although e-cigarettes contain fewer toxins than combustible cigarettes, their long-term cardiovascular and pulmonary effects remain unknown. We aimed to assess the association between self-reported chest pain and e-cigarette use.